Chronic Intermittent Mild Whole-Body Hypothermia Is Therapeutic in a Mouse Model of ALS - Lee J. Martin; Mark V. Niedzwiecki; Margaret Wong (Cells, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that causes motor neuron degeneration. There are no cures or effective treatments for ALS. Therapeutic hypothermia is effectively used clinically to mitigate mortality in patients with acute acquired brain injury and in surgical settings to minimize secondary brain injury. The efficacy of therapeutic hypothermia in chronic neurodegenerative disorders has not been examined. We tested the hypothesis that mild hypothermia/cold acclimation is therapeutic in a transgenic mouse model of ALS caused by expression of mutated human superoxide dismutase-1 gene. At presymptomatic stages of disease, body temperatures (oral and axial) of mutant male mice were persistently hyperthermic (38–38.5 °C) compared to littermate controls, but at end-stage disease mice were generally hypothermic (36–36.5 °C). Presymptomatic mutant mice (awake-freely moving) were acclimated to systemic mild hypothermia using an environmentally controlled chamber (12 h-on/12-off or 24 h-on/24 h-off) to lower body temperature (1–3 °C). Cooled ALS mice showed a significant delay in disease onset (103–112 days) compared to normothermia mice (80–90 days) and exhibited significant attenuation of functional decline in motor performance. Cooled mice examined at 80 days had reduced motor neuron loss, mitochondrial swelling, and spinal cord inflammation compared to non-cooled mice. Cooling attenuated the loss of heat-shock protein 70, mitochondrial uncoupling protein-3, and sumoylated-1 (SUMO1)-conjugated proteins in skeletal muscle and disengaged the mitochondrial permeability transition pore. Cooled ALS mice had a significant extension of lifespan (148 ± 7 days) compared to normothermic mice (135 ± 4 days). Thus, intermittent systemic mild hypothermia is therapeutic in mouse ALS with protective effects manifested within the CNS and skeletal muscle that target mitochondria.